Uji Organoleptik Susu Pasteurisasi Kombinasi Ekstrak Bunga Telang (Clitoria ternatea L) dengan Persentase Berbeda - Ramadani, Dewi; Indriani, I; Parawansya, Akram; Agsa, Muh. Fachrin; Faridah, Rajmi; Muhlis, Fadliah (Jurnal Galung Tropika, 2023)
Indonesian people'sinterest in milkconsumptionis minimal compared to several developed countries. One of the factors causing minimal milk consumptionis the unattractive base color of the milk. The solutionis by diversifying dairy products with a combination of butterfly pea flower extract (Clitoria ternatea) as a natural coloring. Butterfly pea flowers (Clitoria ternatea) contain flavonoids as natural dyes and anthocyanins, which are bioactive components that have functional value as antioxidants. Besides being anantioxidant, butterfly pea flowers (Clitoriater natea) also function as antibacterial, anti-inflammatory, analgesic, anti-diabetic, anti-cancer, and anti-histamine. This research aims to determine the percentage of butterfly pea flower extract (Clitoria ternatea L) in making pasteurized milk, which has the best hedonic quality in termsof color, aroma, taste, and level of preference. The research design applied was a Completely Randomized Design (CRD) with 4 treatmentsand 4 replications. Treatment P0: Milk (control), P1: Milk + 10% butterfly pea flower extract, P2: Milk + 15% butterfly pea flower extract, P3: Milk + 20% butterfly pea flower extract and P4: Milk + 25% butterfly pea flower extract. The variables observed are hedonic quality, including color, aroma, taste, and level of liking. The research showed that pasteurized milk with a combination of butterfly pea flower extract, namely the P3 treatment (Milk + 20% butterfly pea flower extract), was the best color and taste. Mean while, the highest level of liking was P4 (Milk + 25% butterfly pea flower extract) in terms of aroma.